La mediación : Åuna verdadera herramienta de justicia restaurativa? (2018)
Mediation is a tool for restorative justice introduced in Law 906 of 2004. This essay will seek to clarify whether, in light of the existing literature on the topic of Restorative Justice, mediation, as conceived in the Colombian criminal law, is within the general standards of Restorative Justice.